ANALISIS KEPEDULIAN PELAKU USAHA TERHADAP PROTOKOL KESEHATAN CORONAVIRUS DISEASE ( COVID-19 ) PADA PUSAT PERBELANJAAN MODERN DI KOTA BENGKULU - Suswati Nasution; Tito Irwanto (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
The concern of business actors during the Covid-19 pandemic is an important and very influential thing on the economy. In the midst of the COVID-19 pandemic, people think several times to visit shopping centers because of their concern that they will be infected with the coronavirus disease or covid-19, this will undoubtedly disrupt the running of the economy and indirectly impact the decline in turnover of business people. will have an impact on small traders who are around the location of the shopping center. This epidemic that has been going on for a very long time has caused the Government to issue a new policy by opening the faucet of the new normal discourse. Where to overcome the worsening economic situation, especially the trade and business sectors, not to get worse, the new normal discourse is echoed, where in the new normal era, people are expected to return to their normal activities provided that they comply with the Covid -19 health protocol. The community welcomes this discourse, those who were previously silent and doing all activities at home, have begun to make plans to carry out activities outside the home, including visiting a shopping center. For this reason, it is necessary to see the extent to which business actors care about health protocols at their place of business, so that visitors feel safe shopping without fear of contracting the virus.The perceptions of these business actors in this shopping center are very much needed to find out whether their concerns have an impact on increasing shopping center visits and can increase business income. With survey research and the method used is descriptive analytical quantitative. By taking samples from the population of business actors in two modern shopping centers in the city of Bengkulu, Bencoolen Mall and Mega Mall, and using a questionnaire as a data collection tool, 40 respondents were obtained, then the respondent's data and respondents' statements were processed using distribution On average with a Likert scale measuring instrument 5, while determining the characteristics of respondents using the frequency distribution with the help of SPSS as data processing software. The results of data processing show that business actors in two modern shopping centers in the city of Bengkulu are categorized as good in implementing the protocol. health Covid-19. Of course this is not a final result, stakeholders are expected to be able to increase the category to Very Good. So that the shopping center becomes a comfortable place for visitors even though the Covid-19 epidemic period has not ended.Keywords: Business Actor Concern, Covid-19 Prevention Protocol, Modern Shopping Center